PROBLEMS WITH THE QUALITY OF PERSONNEL TRAINING FOR AGRITOURISM IN IVANO-FRANKIVSK REGION - Alla Boichuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is devoted to the research of modern state of personnel training for agritourism in Ivano-Frankivsk region. It is noted that in the region there are no qualified specialists in this field who are well aware of the recreational and environmental potential of their region, are able to apply this knowledge for the dissemination of agritourism and to improve the quality of services. It is marked that the education in the field of agritourism helps to improve the quality of services and the competitiveness of the agritourism industry in the region. The author makes the analysis of the survey of agritourism complexes employees and tourists concerning the readiness of employees to the professional activity. As a result of the research the main factors that affect the quality of personnel training for agritourism in the region and the main requirements for the specialists in agritourism are identified.